Effect of cervical flexion and extension on thoracic sagittal alignment. (9th October 2019) - Konishi, Takamitsu; Endo, Kenji; Aihara, Takato; Matsuoka, Yuji; Suzuki, Hidekazu; Takamatsu, Taichiro; Kusakabe, Takuya; Sawaji, Yasunobu; Nishimura, Hirosuke; Murata, Kazuma; Yamamoto, Kengo
Introduction: The cervical spine has the largest sagittal motion in the whole spine, and cervical alignment affects the thoracic sagittal alignment. However, the effects of cervical flexion and extension on thoracic sagittal alignment have not been investigated in detail. The purpose of this study was to analyze the change of thoracic sagittal alignment following cervical flexion and extension. Subjects and methods: A total of 55 consecutive patients (42 men and 13 women; average age 49.1 years) who presented to our department with spinal degenerative disease between January 2016 and September 2017 were enrolled in our study. Subjects with a history of trauma, infection, tumor, inflammatory disease, ossification, or cervical deformities, and those who had undergone spinal surgery were excluded. The following parameters were analyzed: occipito-axial angle (O–C2), C2 slope (C2S), C2–C7 angle, T1 slope (T1S), thoracic kyphosis, T1–T4 angle, T5–T8 angle, T9–T12 angle, lumbar lordosis, sacral slope, pelvic tilt in cervical flexion, neutral, and extension. Results: Cervical flexion significantly decreased O–C2, C2–C7 angles and T1S, and increased C2S. Cervical extension conversely changed these parameters. At cervical flexion, the correlation of C2–C7 angle with thoracic parameters was maintained, except for the T1–T4 angle. At cervical extension, the correlation was observed with T1S and T1–T4 angle. Conclusion: Cervical flexion affects the T1S and T5–T8 angle, but there is no significant change in T1–T4 and T9 and lower spino-pelvic columns. This study suggests that T2–T4 can be considered as a stable distal end when cervical long fixation for corrective surgery is performed.